(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The 6TM family of K channels comprises the voltage-gated KV subfamilies, the EAG subfamily (which includes hERG channels), the Ca2+-activated Slo subfamily (actually with 7TM, termed BK) and the Ca2+-activated SK subfamily. These channels possess a pore-forming α subunit that comprise tetramers of identical subunits (homomeric) or of different subunits (heteromeric). Heteromeric channels can only be formed within subfamilies (e.g. Kv1.1 with Kv1.2; Kv7.2 with Kv7.3). The pharmacology largely reflects the subunit composition of the functional channel.